An Eliminativist Approach to Vulnerability - Wrigley, Anthony ca. 20./21. Jh. (Bioethics, 2015)
The concept of vulnerability has been subject to numerous different interpretations but accounts are still beset with significant problems as to their adequacy, such as their contentious application or the lack of genuine explanatory role for the concept. The constant failure to provide a compelling conceptual analysis and satisfactory definition leaves the concept open to an eliminativist move whereby we can question whether we need the concept at all. I highlight problems with various kinds of approach and explain why a satisfactory account of vulnerability is unlikely ever to be offered if we wish the concept to play a genuinely explanatory role in bioethical contexts. I outline why an eliminativist position should be taken with regard to this concept in light of these concerns but mitigate some of the severity of this position by arguing that we can still make sense of retaining our widespread use of the term by viewing it as nothing more than a useful pragmatic linguistic device that acts as a marker to draw attention to certain kinds of issue. These issues will be entirely governed by other, better understood ethical concepts and theories.